2006
DOI: 10.1103/physrevb.74.245109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of theoretical and experimental dielectric functions: Electron energy-loss spectroscopy and density-functional calculations on skutterudites

Abstract: We explore the possibility of combining density functional theory ͑DFT͒ and electron energy loss spectroscopy ͑EELS͒ to determine the dielectric function of materials. As model systems we use the skutterudites CoP 3 , CoAs 3 , and CoSb 3 which are prototypes for thermoelectric materials. We achieve qualitative agreement between the theoretically and experimentally obtained low energy-loss spectra and dielectric function. Some of the remaining discrepancies may be caused by the challenge of refining the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…The Dudkin model is generally confirmed by site-and symmetry-projected density of states from DFT calculations. Typically, a large overlap between the TM 3d and Pn 3p states is observed, 7,9,32 indicating bonding through hybridization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dudkin model is generally confirmed by site-and symmetry-projected density of states from DFT calculations. Typically, a large overlap between the TM 3d and Pn 3p states is observed, 7,9,32 indicating bonding through hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…2 Tailoring their electronic and thermal properties is therefore possible, and modified skutterudite materials are indeed among the most promising of a new generation of thermoelectric materials. [2][3][4] Several theoretical [5][6][7][8] and experimental [9][10][11][12][13] studies of the electronic structure of Cobased skutterudites have been performed. A particular interesting signature of the bonding and electronic structure is the occupancy of the 3d states of Co. Anno et al 12 used x-ray photoelectron spectroscopy ͑XPS͒ to study the occupied states of CoAs 3 and CoSb 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, transition metals usually display a single, broad plasmon peak, and the Drude model often fails to predict their plasmon energies. This is opposed to simple metals such as Na, Al and semiconductors such as Si, Ge, which have sharp plasmon peaks near the predicted value (Prytz et al, 2006). An alternative mechanism of energy loss, involving the transfer of energy from a transmitted electron to a single atomic electron within the specimen is also very common for this type of materials.…”
Section: Low Loss Eels Studymentioning
confidence: 99%
“…For electrons close to the Fermi level, this second mechanism can be regarded as competing with plasmon excitation and is coupled to it. The possible effects of single-electron excitation include broadening and/or shift of the plasmon peak and the addition of fine structure (Egerton, 1986;Prytz et al, 2006).…”
Section: Low Loss Eels Studymentioning
confidence: 99%
“…However, in the second method the Seebeck coefficient changes to positive approximately at 540 K. The reason is that the hole mobility is much larger than the electron mobility in the temperature range higher than 540 K [12], at which intrinsic excitation commences. It has been reported that the intrinsic CoSb3 shows the p-type conductivity [13,14]. In this study, the low purity of Co (99.8%) may be the reason for the appearance of n-type conductivity initially [15].…”
Section: Preprints (Wwwpreprintsorg) | Not Peer-reviewed | Posted: mentioning
confidence: 81%